On Plane Curves with Double and Triple Points - Abdallah, Nancy (Mathematica Scandinavica, 2016)
We describe in simple geometric terms the Hodge filtration on the cohomology H^*(U) of the complement U=P^2 C of a plane curve C with ordinary double and triple points. Relations to Milnor algebra, syzygies of the Jacobian ideal and pole order filtration on H^2(U) are given.